Tropical tannin for engineering application: a review - Zulkafli, Hassan; W. A., Ibrahim; Azizul Helmi, Sofian; Noor Aishah, Rosli (2018)
There is a great concern to protect the steel surfaces from corrosion phenomenon in the environment of oil and gas industry. Several approaches have been proposed to introduce alternative new compounds in the paint which are green sources that can reduce environmental risks. Tannins in actuality are large and diverse family of phenolic compound with varying structure and widely distributed through the plant kingdom. It has myriad supplemental functions in a plant’s life cycle, as protective tissue and defense strategies. The phenolic compound is consist of hydroxyl group bonded to an aromatic compound and has the properties to interact with aqueous solution. Phenolic compound is an active compound due to the lower bond dissociation energies of OH group and easier to lose H atom [1]. Hence, tannin containing enough hydroxyl group for encourage effective cross linking of other compounds. Tannin can be divided into two groups called condensed tannins and hydrolysable tannins. Hydrolysable tannins are hydrolysed by enzyme or acid and can be subdivided into ellagitannin and gallotannin while condensed tannins are not readily hydrolysable to simpler molecules and they do not contain a sugar moiety. Condensed tannin have the ability to synthesize mixtures of polymers and oligomers that makes their chemistry typically quite demanding. Tannin contain four flavonoid namely: catechin, epitechin, epigallocatechin and epicatechin gallate which is showed in Figure 1. Due to its flavonoid monomer, tannin have the prospective as corrosion inhibitors for steel in acidic environment [2].